A Particular Use of Endobag®: Extraction of Rectal Foreign Bodies - G. Terrosu; V. Cherchi; S. Calandra; A. Esposito; M. Marino; D. Berretti; A. Risaliti (Case Reports in Medicine)
Introduction. The incidence of foreign bodies (FBs) in the rectum has recently increased. FB removal by the transanal way or by colonoscopy is generally feasible and only in few cases surgery is strictly necessary. Due to FB dimensions or rectum and colon anatomy, sometimes it may represent a challenge. Materials and Methods. Two cases of FB inserted in the rectum were treated in our institute. They underwent surgery using Endobag, a laparoscopic surgical device. The device was inserted through the anus in order to catch and remove the FB. Results. Both the procedures were easily performed, without any complication. Conclusions. The use of Endobag seems to be a good and effective way to remove FB from rectum.